Pencegahan Kecacingan Melalui Pendampingan Pembiasaan Pola Hidup Bersih Sehat dan Pemeriksaan Kecacingan pada Anak-Anak Di SD Negeri 3 Konawe Selatan: Pencegahan Kecacingan Melalui Pendampingan Pembiasaan Pola Hidup Bersih Sehat dan Pemeriksaan Kecacingan pada Anak-Anak Di SD Negeri 3 Konawe Selatan - Fusvita; Aulya, Muhammad Sultanul; Idris, Sri Aprilianti; Fusvita, Angriani; firdayanti, Firdayanti; Umar, Ani; Idris, Kemal; Wenty, Darmayanita (Universitas Mataram, 2023)
Worm infections caused by Soil Transmitted Helminth (STH) are intestinal nematode worms which are transmitted through the soil in their life cycle. The various kinds of nematode class worms that are known are roundworms (Ascaris Lumbricoides), whipworms (Trichuris trichiura) and hookworms (Ancylostoma duodenale and Necator americanus). Worms have a very bad effect on health, in children worms will have an impact on learning disorders, decreased quality of intelligence and reduced nutritional intake. The aim of this community service activity is to provide socialization on the prevention of worms through assistance in getting used to a clean, healthy lifestyle and checking for worms among children at SD Negeri 3 Konawe selatan. The respondents in this activity were children at SD Negeri 3 Konawe selatan and 31 stool samples were obtained. The results of stool examination using the direct method on 31 children's stool samples did not find positive samples and 31 children's stool samples did not contain intestinal nematode worm eggs.